2008
DOI: 10.1177/230949900801600118
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Embolisation in Benign Bone Tumour Excision

Abstract: Purpose. To assess the role of preoperative embolisation in benign bone tumour excision. Methods. 3 men and 3 women aged 19 to 35 (mean 23) years with either a giant cell tumour or an aneurysmal bone cyst in limb girdle sites underwent preoperative embolisation a day prior to wide local excision by the same surgeon. Tumour size, blood loss, wound healing, infection, and tumour recurrence were assessed. Results. The mean total blood loss was 391 (range, 100-980) ml. No blood transfusion was needed. No patient h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…18 Retrospective EBL = 1100-2600 mL MBL = 1400 mL BT = 0-8 units Kobayashi et al [27] 2012 62 Retrospective EBL = 250-11000 mL MBL = 2554 mL BT = 0-28 units Al-Hadithy et al [20] 2011 26 Retrospective EBL = 100-1800 mL BT = 0-3 units Zhang et al [32] 2009 47 Retrospective EBL = 705 ± 120 mL BT = 689 ± 133 mL Lee et al [13] 2008 6 Prospective EBL = 200-830 mL BT = Nil Our study 2012-2013 26 (study group) Case control study For study group EBL = 250-2900 mL BT = 0-1400 mL 28 (control group)…”
Section: Ref Year No Of Patients Type Of Study Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Retrospective EBL = 1100-2600 mL MBL = 1400 mL BT = 0-8 units Kobayashi et al [27] 2012 62 Retrospective EBL = 250-11000 mL MBL = 2554 mL BT = 0-28 units Al-Hadithy et al [20] 2011 26 Retrospective EBL = 100-1800 mL BT = 0-3 units Zhang et al [32] 2009 47 Retrospective EBL = 705 ± 120 mL BT = 689 ± 133 mL Lee et al [13] 2008 6 Prospective EBL = 200-830 mL BT = Nil Our study 2012-2013 26 (study group) Case control study For study group EBL = 250-2900 mL BT = 0-1400 mL 28 (control group)…”
Section: Ref Year No Of Patients Type Of Study Resultsmentioning
confidence: 99%
“…Another study reported by Kobayashi et al [27] used PVA and embosphere as embolising material. In study reported by Lee et al [13] only gelfoam was used for embolization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embolisation reduces tumour vascularity (Fig. ) and assists in tumour excision with an adequate margin . The aim of embolisation is to occlude as much of the tumour arterial supply as possible, without sacrificing the non‐targeted arteries .…”
Section: Technique and Embolic Agentsmentioning
confidence: 99%
“…Embolisation of bone tumours has been accepted as a useful treatment for various reasons. For those tumours that require surgical resection, pre‐operative embolisation reduces intra‐operative blood loss . For those inoperable tumours, palliative control of pain or bleeding can be achieved .…”
Section: Introductionmentioning
confidence: 99%